Mekanisme Pengelolaan Zakat Fitrah Berbasis Kultural Dalam Masyarakat Samalanga - Syeh Khaliluddin (Fakultas Syariah dan Ekonomi Islam, 2021)
This research is to be able to describe the management of zakat fitrah in a society that is full of cultural values ​​by always adhering to the legal consequences of fiqh starting from the determination of amil, collection methods, categories of assets issued, determination of mustahik and their distribution to mustahik. The research method used is descriptive qualitative by conducting interviews, observations and documentation research to obtain information both primary and secondary. The results of the research show that in the management of zakat fitrah, residents are still contaminated with traditional cultural systems that have been in effect for a long time, namely relating to amil which is agreed upon by the community and raised by the sub-district government from Imum gampong, where the collection and distribution is carried out in the meunasah, the procedure for collecting as well as the distribution of zakat fitrah by amil in the Samalanga sub-district through the collection stage with the technique of being delivered directly by muzakki on the eve of Eid al-Fitr to the village meunasah, the determination of senif and mustahik and the distribution is also carried out that same night with the technique of delivering to the mustahik's house by an officer selected by the amil . The category of property given for zakat fitra is only rice with a dose of 2 bamboo or equivalent to +2.6 kilograms per muzakki soul.